2017
DOI: 10.1016/j.cmi.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The detection of microbial DNA but not cultured bacteria is associated with increased mortality in patients with suspected sepsis—a prospective multi-centre European observational study

Abstract: Presence of microbial DNA in patients with suspected sepsis might define a patient group at higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…While the presence of bacterial DNA in these blood samples did not indicate the presence of viable organisms, it suggested that the clinical blood cultures were under-representing the presence of bloodstream infections in this cohort. These results are comparable to similar studies using molecular diagnostic platforms have also reported under representation of bloodstream infections when blood culture diagnostics were compared to PCR based methods [ 13 , 51 – 55 ]. This study also outlined several cases where the bacterial DNA amplified from the blood sample had good concordance with bacterial pathogens that were recovered from pertinent clinical diagnostic cultures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While the presence of bacterial DNA in these blood samples did not indicate the presence of viable organisms, it suggested that the clinical blood cultures were under-representing the presence of bloodstream infections in this cohort. These results are comparable to similar studies using molecular diagnostic platforms have also reported under representation of bloodstream infections when blood culture diagnostics were compared to PCR based methods [ 13 , 51 – 55 ]. This study also outlined several cases where the bacterial DNA amplified from the blood sample had good concordance with bacterial pathogens that were recovered from pertinent clinical diagnostic cultures.…”
Section: Discussionsupporting
confidence: 89%
“…However, the prevalence of polymicrobial DNA in whole blood from septic patients suggested there could be greater propensity for polymicrobial infections in sepsis than currently appreciated using cultivation-dependent and broth-enrichment based approaches. Similar results from direct blood analysis have shown utility of molecular profiling for identification of microbial DNA and its utility as an additional tool for sepsis diagnostics [ 13 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 77%
“…Thus, PCR allows for early diagnosis of sepsis and rapid treatment (antibacterial or antifungal), which lowers the treatment/hospital cost (LIESENFELD et al, 2014). Although, microbial DNA can be found even in healthy individuals, a previous study showed that the presence of microbial DNA in the blood of human patients with sepsis indicated a high risk of death (O'DWYER et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the same group ( 16 ) identified 84 BC-negative PCR/ESI-MS-positive microorganisms, of which 42 microorganisms (50%) had support from clinical findings. In a European ICU sepsis study ( 27 ) (a subgroup study of that described in reference 10 ), the 28-day mortality was found to be higher in patients with BC-negative PCR/ESI-MS-positive results than in patients with BC-negative PCR/ESI-MS-negative results (42% versus 26%; P = 0.001). This association with disease severity may perhaps be due to true bloodstream infection in a substantial proportion of cases with BC-negative PCR/ESI-MS-positive results.…”
Section: Discussionmentioning
confidence: 97%